2010
DOI: 10.1111/j.1365-2672.2010.04730.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of Campylobacter in river water and waterfowl within a watershed in southern Ontario, Canada

Abstract: Aims:  Quantitative PCR and a culture method were used to investigate Campylobacter occurrence over 3 years in a watershed located in southern Ontario, Canada that is used as a source of drinking water. Methods and Results:  Direct DNA extraction from river water followed by quantitative PCR analysis detected thermophilic campylobacters at low concentrations (<130 cells 100 ml−1) in 57–79% of samples taken from five locations. By comparison, a culture‐based method detected Campylobacter in 0–23% of samples. Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 45 publications
7
58
0
Order By: Relevance
“…Most studies screening for the presence of Campylobacter in waterfowl have used cumbersome culture-based methods that are known to have low recovery yields and to potentially underestimate the number of species in a given sample (33). As a result, it is unclear what the prevalence and densities of different Campylobacter spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies screening for the presence of Campylobacter in waterfowl have used cumbersome culture-based methods that are known to have low recovery yields and to potentially underestimate the number of species in a given sample (33). As a result, it is unclear what the prevalence and densities of different Campylobacter spp.…”
mentioning
confidence: 99%
“…Based on previous culture estimations, Campylobacter has been estimated to range from 3.0 ϫ10 3 to 1.7 ϫ 10 7 CFU/g (wet weight) in the ring-billed gull (L. delawarensis) droppings (22), with lower estimates from herring gull and common black-headed gull (L. ridibundus) excreta (1.8 ϫ10 2 to 4.9 ϫ 10 6 CFU/g and from 7.4 ϫ 10 2 to 1.7 ϫ 10 5 CFU/g, respectively) (9). The differences between the higher estimates by qPCR assays and the lower culture-based numbers may in part reflect active but nonculturable campylobacters (25,33). The unidentified campylobacters from California gulls (which represented nearly 92% of the clones) require further examination and may represent novel species that are problematic to culture using currently available media.…”
mentioning
confidence: 99%
“…Similarly, it was suggested that the filtration of large volumes (e.g. 1 000 to 4 000 mL) may be appropriate for the determination of campylobacters in environmental waters [80,83]. With groundwater, the filtration of a 10 mL sample failed to recover campylobacters [84], while, successful detection of Campylobacter was achieved with the filtration of 100 to 500 mL of groundwater [17].…”
Section: Detection In Water and Wastewatermentioning
confidence: 99%
“…Many investigations of Campylobacter spp. in water have used a 42°C incubation temperature (9,(19)(20)(21)(22)(23)(24)(25). However, other water studies have used a 37°C incubation temperature (26)(27)(28).…”
mentioning
confidence: 99%
“…These three species can commonly occur in the gastrointestinal tracts of humans and other animals, including bovines, pigs, and birds. Sea gulls and several other wild birds can be an important source of Campylobacter spp., such as C. jejuni and C. lari (3,8,9). Campylobacters from the feces of birds or domestic and wild animals, municipal sewage discharges, or agricultural runoff can contaminate water (3), and water is an established vehicle for the transmission of these species to human and domestic animals, leading to outbreaks of waterborne disease.…”
mentioning
confidence: 99%